Medication Adherence and Patient Outcomes: Investigating Strategies to Improve Patient Compliance: Exploring the Impact of Medication Adherence on Patient Outcomes in Saudi patients with Type 2 Diabetes (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Medication adherence is defined as taking medications as advised and prescribed by healthcare professionals for stated duration. Diabetes mellitus (DM) is one of the most common chronicillnesses in Saudi Arabia. This study aimed to document medication adherence in Saudi patients withtype 2 diabetes. A quantitative cross-sectional study was conducted in Saudi out-patients with type 2 DMin the city of Khobar, Saudi Arabia. The study used the General Medication Adherence Scale (GMAS) todocument medication adherence in this population. Data was analyzed through SPSS version 23. Studywas ethically approved. Data was collected from 212 patients. Few patients (35.8) had high adherenceto anti diabetic medications. The correlation between HbA1c level and adherence score was negative andsignificantly strong (ρ = -0.413, p < 0.0001). Most patients (N = 126, 59.4) modified their medicationtherapy during month of Ramadan and on Eid occasion. Education level was not a determinant ofadherence in this population. The medication adherence score for the entire indicating moderateadherence Medication-related factors such as the number of medications prescribed, medicationcomplexity This study highlighted that medication adherence is influenced by religious and socialfactors. Patient counseling is required to improve patient beliefs and increase awareness of adhering toprescribed anti diabetic pharmacotherapy. A pharmacist can play constructive role of a disease educatorand patient counselor.